ANXIETY AND ITS SIGNIFICANCE IN THE STRUCTURE OF SOMATOFORM DISORDERS IN CHILDREN AND THE ROLE OF SEROTONINE AND TRIPTOPHAN IN THEIR NASCENCE - Pypa, L.V.; Lysytsia, Yu.N.; Svistilnik, R.V.; Bulat, L.M. (World of Medicine and Biology, 2020)
The work was aimed to study the confidence and significance of anxiety in the occurrence of somatoform disorders (SD) in children, to establish the role of serotonin and tryptophan in its development. 111 children were diagnosed with SD. In 109 (98,2%) children were diagnosed with excessive anxiety. Serotonin levels in children with personality and reactive anxiety were 1,16 ± 0,33 μmol/l and 1,17 ± 0,33 μmol/l, respectively and were lower compared to the control group, where its level reached 1,35 ± 0,34 μmol/l (p
Keywords: somatoform disorder; anxiety; serotonin; tryptophan; children